How Children with Complex Communication Needs Communicate Their Menstrual Needs: ICT-Based Alternative and Augmentative Communication - RIZQITA, ALYA JILAN; Aprilia, Imas Diana; Sunardi, s; Maryanti, Rina; Bela, Muhammad Rafi Wirdan Assyakir Tandu; Juhanaini, J; Putri, Lamina Amalia (Jurnal Asesmen Dan Intervensi Anak Berkebutuhan Khusus, 2024)
The rapid development of ICT can be utilized in this innovation. Using Android-based technology, the Alternative and Augmentative Communication (AAC) system can be used to help children with complex communication needs (CCN) express their needs in their menstrual cycle and realize the importance of reproductive health if their menstrual cycle is irregular. This research aims to develop alternative and augmentative ICT-based communication designs for adolescent girls with CCN. The subject in this research was a teenage girl with CCN who had menstruated. The method in this research uses descriptive qualitative. This research involves one subject (single subject) which is used as a mode in developing applications. The results of this research are in the form of an application design to help teenage girls with CCN communicate to express their needs during menstruation. This application design is also equipped with a calendar totrack the menstrual cycle. content of items needed during menstruation content is especially good because it will be appropriate for subjects who have difficulties expressing their wants and needs to family, teachers, or friends in the school environment. Menstrual calendar content can help subjects andparents identify the regularity of the subject's menstrual schedule. The design of this application is expected to help young women and CCN communicate, so that CCN can express their needs during menstruation.